The Development of Leishmania tropica in Sand Flies (Diptera: Psychodidae): A Comparison of Colonies Differing in Geographical Origin and a Gregarine Coinfection - Jancarova, Magdalena; Hlavacova, Jana; Volf, Petr (Journal of medical entomology, 2015)
Phlebotomus sergenti Parrot, 1917 is the main vector of Leishmania tropica; however, its broad geographical range and molecular heterogeneity suggest possible variability in vector competence. We infected laboratory-reared P. sergenti originating from Turkey and Israel to compare their susceptibility to L. tropica. In both tested groups, heavy late-stage infections with the presence of metacyclic forms and colonization of the stomodeal valve were observed. The similar development of Leishmania in both sand fly colonies indicates that the different geographical origin of P. sergenti is not reflected by a different vector competence to L. tropica. Additionally, we tested the effect of the gregarine Psychodiella sergenti on L. tropica coinfections; no apparent differences were found between P. sergenti infected or not infected by gregarines.
Keywords: vector competence; Psychodidae; Insect Vectors; Leishmania tropica; Phlebotomus sergenti; Apicomplexa; gregarine; Animals; Female; ženské pohlaví; hmyz - vektory; Host-Parasite Interactions; zvířata; interakce hostitele a parazita; coinfection